2013
DOI: 10.4103/0377-4929.118661
|View full text |Cite
|
Sign up to set email alerts
|

Cytohistological correlation in diagnosis of lung tumors by using fiberoptic bronchoscopy: Study of 200 cases

Abstract: Bronchial brushing and washing cytology in combination with imprint cytology aids in the diagnosis of lung tumors. Therefore, all these techniques may be used concurrently along with bronchial biopsy to diagnose lung tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
7
19
0
1
Order By: Relevance
“…10 From the above we conclude that squamous cell carcinoma is the most common histological type of lung cancer as is seen in our study also. Small cell carcinoma is the second commonest type of lung cancer in our study which is comparable with the studies done by and Sheema et al and Bodh et al 10,25 Our study is at variance to western literature where incidence of adenocarcinoma has surpassed squamous cell carcinoma. 26,27 In the present study BAL was positive in 301 cases.…”
Section: 22supporting
confidence: 81%
See 1 more Smart Citation
“…10 From the above we conclude that squamous cell carcinoma is the most common histological type of lung cancer as is seen in our study also. Small cell carcinoma is the second commonest type of lung cancer in our study which is comparable with the studies done by and Sheema et al and Bodh et al 10,25 Our study is at variance to western literature where incidence of adenocarcinoma has surpassed squamous cell carcinoma. 26,27 In the present study BAL was positive in 301 cases.…”
Section: 22supporting
confidence: 81%
“…7 Bronchial washing (BW), bronchoalveolar lavage (BAL) and brushing specimens can also be obtained for cytopathological examination. [8][9][10][11] Historically, 4 specimens have been shown to be adequate for optimal diagnostic yield in central lesions. 12 The diagnostic sensitivity of bronchial biopsy in diagnosing lung malignancies ranges from 65-83%.…”
Section: Introductionmentioning
confidence: 99%
“…The male: female ratio of present study was 2.7:1. Bodh et al 14 found in their study that male: female ratio is 3.35:1 whereas Sareen et al 3 showed male: female ratio of 8.4:1. Cough and shortness of breath was the most common complaints.…”
Section: Discussionmentioning
confidence: 85%
“…Brushing yielded highest diagnostic yield (16.4%) compared to aspiration (14.0%) and BAL (11.6%), although the differences between the various techniques were not statistically significant (p=0.08). Bodh et al [14] and Stringfield et al [15] recommended the use of bronchial washings and brushings in addition to biopsy to increase the diagnostic yield. In our study, we found the diagnostic yield in the endobronchially non-visible group to be highest for bronchial brushings (40.65%) followed by bronchial washings (28.57%) and lastly by endobronchial biopsy (18.6%).…”
Section: Discussionmentioning
confidence: 99%